Kemampuan Guru IPA dalam Pelaksanaan Pembelajaran Kurikulum 2013 Kelas VII SMP Negeri Se-Kota Surakarta Tahun Ajaran 2014/2015 Kemampuan Guru IPA Kelas VII dalam Pelaksanaan Pembelajaran Kurikulum 2013 SMP Negeri Se-Kota Surakarta Semester Genap Tahun Ajaran 2014/2015 - Primadianti, Rizky Ika, Drs. Djumadi, M.Kes (2015)
The purpose of this study was to determine the ability of the preparation of lesson plans and curriculum based learning implementation in 2013 by seventh grade science teacher at SMP Negeri Surakarta academic year 2014/2015. The study was conducted in SMP Negeri 1 Surakarta, SMP Negeti 4 Surakarta, and SMP Negeri 12 Surakarta, the subject of this study is the seventh grade science teacher at SMP Negeri Surakarta, the object of this study is the lesson plan drawn up by a junior high school teacher of Surakarta class VII and the implementation pemebelajarannya using the curriculum of 2013. This type of research is descriptive qualitative data collection techniques done with the documentary study, observation, and interviews Junior High School science teacher Surakarta class VII. The result showed that the ability of teachers to prepare lesson plans is teacher A (87.5%), teachers B (84.6%), teachers C (81.2%). The ability of teachers in the implementation of the acquired learning outcomes A teacher (94.4%), teachers B (66.6%), and teachers C (81.9%). Overall grade science teacher's ability VII arrange RPP curriculum at SMP Negeri Surakarta academic year 2014/2015 categorized as very good (84.4%) and the implementation of learning categorized as excellent (81.4%).